Spinal Injuries Caused By The Acceleration Of Ejection. Issue 1 (1st March 2002) - Lewis, ME
Abstract : The speed and altititude at which modern military aircraft operate are such that escape can only be achieved by some means of forcibly propelling the aircrew clear of the aircraft. The most common method of doing this is by use of an ejection seat. The use of such seats, whilst generally life saving, exposes aircrew to forces that may be at the limits of human tolerance. Each phase of the ejection sequence is associated with characteristic injury patterns and of particular concern is the occurrence of spinal compression fractures, which are caused by the upward acceleration of the ejection seat. Thorough investigation of aircrew who eject is necessary and magnetic resonance imaging of the spines of these aircrew is now becoming mandatory. Aircrew who sustain stable anterior wedge compression fractures usually require no invasive treatment, but are prevented from flying aircraft fitted with ejection seats for 3-4 months.